Living SMART — A randomized controlled trial of a guided online course teaching adults with ADHD or sub-clinical ADHD to use smartphones to structure their everyday life - Birger Moëll; Linnéa Kollberg; Berkeh Nasri; Nils Lindefors; Viktor Kaldo (Internet Interventions, 2015)
Objective: To evaluate an online intervention for adults with ADHD that aimed to improve organizational skills and attention with the help of smartphone applications. Method: Participants (n = 57) were recruited and assessed through questionnaires and telephone interviews. Diagnoses of ADHD were confirmed for 83% of the participants, 5% most probably had the diagnoses, and 12% did not fulfill all diagnostic criteria despite high levels of symptoms. Participants were randomized between the intervention (n = 29) and a wait-list control group (n = 28). The 6-week intervention involved support from a coach in finding a routine for organizing everyday life with the help of smartphone applications. The primary outcome measure was ASRS Inattention. Secondary outcomes were ASRS sub-scale Hyperactivity and measures of depression, anxiety, stress, quality of life and general level of functioning. Blind evaluators also assessed improvement in organization and inattention at post treatment. Result: The participants receiving the Living Smart course reduced their average scores on ASRS-Inattention from 28.1 (SD = 4.5) to 22.9 (SD = 4.3) which was a significantly larger reduction than found in the control group. 33% of participants were considered clinically significantly improved according to the blind evaluator, compared to 0% in the control group. The same results were found when only participants with a confirmed diagnose were included in the analyses. Conclusion: Adults with ADHD seem to be able to use smartphone applications to organize their everyday life and can be taught how to do this via online interventions.